We can find a formula for nth term of the given sequence as follows:
1, 5, 12, 22, 35
The 1st differences between terms:
4, 7, 10, 13
The 2nd differences :
3, 3, 3
Since it takes two rounds of differences to arrive at a constant difference between terms, the nth term will be a 2nd degree polynomial of the form:
, where c is a constant. The coefficients a, b, and the constant c can be found.
We can form the following 3 equations with 3 unknowns a, b, c:
![1 = a\cdot1^2 + b\cdot1 + c\\5 = \cdot2^2 + b\cdot2 + c\\12 = a\cdot3^2 + b\cdot3 + c](https://tex.z-dn.net/?f=1%20%3D%20a%5Ccdot1%5E2%20%2B%20b%5Ccdot1%20%2B%20c%5C%5C5%20%3D%20%5Ccdot2%5E2%20%2B%20b%5Ccdot2%20%2B%20c%5C%5C12%20%3D%20a%5Ccdot3%5E2%20%2B%20b%5Ccdot3%20%2B%20c)
Solving for a, b, c, we get:
a = 3/2, b = -1/2, c = 0
Therefore, the nth term of the given sequence is:
![\boxed{ a_n = \dfrac{3}{2}n^2- \dfrac{1}{2} n}](https://tex.z-dn.net/?f=%5Cboxed%7B%20a_n%20%3D%20%5Cdfrac%7B3%7D%7B2%7Dn%5E2-%20%5Cdfrac%7B1%7D%7B2%7D%20n%7D)
Answer:
The radius is 4 because since the diameter is 8, the radius is half of the diameter.
-5 This is the answer with the work
23
-28
-----
-5
Answer:
2.27700622339
Step-by-step explanation:
Calculated your welcome
Answer:
11
Step-by-step explanation:
f(3)=(3)^2+2(3)-4
f(3)=9+2(3)-4
f(3)=9+6-4
f(3)=15-4
f(3)=11